Analysis of Power Generation in Electric Scooters With Photovoltaic Panel Integration: A Monte Carlo Simulation Approach - Jae-Hwan Ko; Sung-Min Park (IEEE Access)
This paper analyzes power generation and corresponding additional driving range of various photovoltaic array configurations mounted on an electric scooter. Shared electric scooters have been widely used for short-distance travel. However, they are often unavailable due to insufficient charging after use. To address this issue, photovoltaic panels can be installed on the electric scooter to enable self-charging capabilities. The power generation of photovoltaic panels is affected by continuously varying factors. These include irradiance and shading conditions. These conditions make it difficult to accurately estimate the power generation from a photovoltaic array. This study statistically analyzes the power generation of each photovoltaic array configuration using the Monte Carlo method. The power at the global maximum power point is obtained under random irradiance and shading conditions. Based on these results, the annual power generation and the corresponding additional driving range are calculated.